Determination of Suitable Plant Types in an Irrigation Command Area Using IWQI Method - Sri Wahyuningsih; Elida Novita; Reo Nurdiansyah Ramadhan (The University of Lampung, 2023)
Irrigation water quality of has an essential roles in growing crops by farmers. Agricultural crops can produce superior products if they have good irrigation water quality. Irrigation water quality index (IWQI) is a method to evaluate the quality of irrigation water. This research aim at applying the IWQI in the Sukorejo Secondary Channal to determine suitable plants within the command area with the criteria of tolerance relative to salt. The research was performed by measuring some parameters including the content of Na+ (sodium), Cl– (chloride), HCO3– (bicarbonate), electrical conductivity (EC), and sodium adsorption ratio (SAR), as well as soil permeability. Results of this study showed that the Sukorejo Secondary Channal delivering irrigation water IWQI value of 61.54. Measurements also revealed the soil has a moderate to high level of permeability. Recommendation that can be given is the use plants with moderate amounts of water consumption with moderate tolerance to salt levels. Recommended plants according to IWQI value include corn, soybean, wheat, rice, tomato, cabbage, tobacco, mustard greens, celery, lettuce, papaya, pineapple, pumpkin, peanuts, cucumber, broccoli, tomato, cabbage, eggplant, spinach, potato, watermelon, radish. Keywords: Alkalinity, IWQI, Plants, Salinity, Water quality